La presse catholique irlandaise et la Guerre Civile espagnole. Étude de cas - Pere Soler Paricio (Cahiers de Civilisation Espagnole Contemporaine)
This article analyzes the treatment of the information implemented by the articles, and to a lesser extent also by the bibliographic reviews, linked to the Spanish Civil War, published by the Irish catholic newspapers The Irish Ecclesiastical Record, The Catholic Bulletin and Studies. Previously, the position adopted by the Church of Ireland before the conflict is summarized and the generalized tone under which the majority of Catholic newspapers of the South addressed the issue is analyzed in a synthetic manner. Then, the themes and the preponderant areas of reflection that occupied the essays and recensions linked to the war are identified. That is, the interpretation of the nature of the conflict, the political agenda of the rebellious side, the campaign against Basque nationalists and the defense of Catholic corporatism.